As dimensões do domínio afetivo identificadas em alunos com indicação de fracasso em matemática escolar, durante uma sequência didática envolvendo a geometria - Nobre, Suzana (2018)
This research aims to identify dimensions of the affective domain that emerge from the interactions among students during a didactic sequence involving geometry. The study considered as descriptors of the affective domain the beliefs, the emotions and the attitudes, with its subcategories. The hypotheses formulated presuppose that cognition and affection cannot be investigated separately as affection cannot be investigated separately from the context in which the student is inserted. The subjects of the research were the students of the 5th year of Elementary School in a public school in the city of São Paulo. The focus of the observations fell particularly on the students indicated for the parallel recovery of Mathematics. The data collection was done with the video recordings of the groups and the classroom during the application of the didactic sequence, which was elaborated based on the Theory of Didactic Situations and took into account the cognitive conditions of learning of the geometry. The qualitative analysis of the emotional episodes – extracts of events in the classroom recorded in fragments of video recording was made. The analysis of the data allowed to identify the emergence of beliefs, attitudes and emotions, intrinsically related to learning during the group activities of the didactic sequence. It was also possible to identify the cognitive, affective and intentional components of attitudes that influence behavior. In addition, it showed the interdependence of the dimensions of the affective domain, that is, the influence that one dimension exerts on the emergence of another dimension. Thus, the hypotheses were verified, indicating that it is possible and necessary to definitively break with the dichotomy cognition and affection